2009
DOI: 10.17925/eor.2009.03.02.67
|View full text |Cite
|
Sign up to set email alerts
|

Tensioactive-mediated Transepithelial Corneal Cross-linking – First Laboratory Report

Abstract: Purpose: The aim of this study was to investigate the possibility of delivering riboflavin into the corneal stroma for cross-linking with the aid of a tensioactive substance (benzalkonium chloride), without removing the epithelium, in order to make corneal cross-linking (CXL) a less invasive technique. Methods: Rabbit corneas were cross-linked in vivo without removal of the epithelium, using riboflavin solution 0.1% to which benzalkonium chloride solution was added. The corneas were then examined by light and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous studies report conflicting results on the effects of epithelium-on CXL. While Pinelli and colleagues reported no significant difference in the analyzed parameters between epithelium-on and standard CXL [ 28 ], Wollensak and Iomdina found that the corneal biomechanical stiffening after epithelium-on CXL was about one-fifth compared to the epithelium-off CXL in an animal model [ 4 ]. Other clinical and laboratory studies have reported weaker or no effect of CXL using the epithelium-on method [ 22 , 23 , 25 , 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report conflicting results on the effects of epithelium-on CXL. While Pinelli and colleagues reported no significant difference in the analyzed parameters between epithelium-on and standard CXL [ 28 ], Wollensak and Iomdina found that the corneal biomechanical stiffening after epithelium-on CXL was about one-fifth compared to the epithelium-off CXL in an animal model [ 4 ]. Other clinical and laboratory studies have reported weaker or no effect of CXL using the epithelium-on method [ 22 , 23 , 25 , 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 There is thus inconclusive evidence in the peer-reviewed literature on the aspect of efficacy of some epithelium-on CXL variations. 3,8,26,31,32 The in situ riboflavin application naturally overcomes the first of the 2 obstacles, related to riboflavin penetration through the intact epithelium and in acting as a "blocking" agent against UV-A propagation. This is because the epithelium and Bowman layer, that the UV-A light has to transcend, are not soaked in riboflavin.…”
Section: Discussionmentioning
confidence: 99%
“…The stratified corneal epithelium with tight junctions presents as a lipophilic barrier to the absorption of the hydrophilic riboflavin macromolecule. Standard riboflavin formulations were modified with addition of EDTA, benzalkonium chloride (BAC), trometamol, which loosen up the epithelial junctions, enhancing the permeability and riboflavin diffusion across the epithelium and superficial stroma 6,10. However cumulative dose of BAC in ParaCel alone may result in damage to the superficial corneal epithelial cells11 as its effect is concentration and dose dependent 12.…”
Section: Introductionmentioning
confidence: 99%
“…Standard riboflavin formulations were modified with addition of EDTA, benzalkonium chloride (BAC), trometamol, which loosen up the epithelial junctions, enhancing the permeability and riboflavin diffusion across the epithelium and superficial stroma. 6 , 10 However cumulative dose of BAC in ParaCel alone may result in damage to the superficial corneal epithelial cells 11 as its effect is concentration and dose dependent. 12 A recent two stage application of initial ParaCel containing BAC followed by BAC and dextran free vibeX Xtra combined with accelerated UVA irradiance protocols (total energy dose of 5.2j/cm 2 or 7.2 j/cm 2 ), reduced riboflavin soak time and promoted epithelial integrity, 13 maximizing patient comfort and disease stabilization.…”
Section: Introductionmentioning
confidence: 99%